Rewriting the Earth: Ecolinguistic Task Based Activities to Enhance Writing Skills in English - Hariati, Puji (English Teaching and Linguistics Journal (ETLiJ), 2026)
English writing remains a significant challenge for many secondary school students in Indonesia, particularly in expressing ideas coherently, organizing structure, and using appropriate vocabulary. This study investigates the effectiveness of integrating Ecolinguistic Task-Based Activities (ETBAs) in improving the English writing skills of Grade X students at Yayasan Pendidikan Nazhirul Asrofi Medan. Grounded in Task-Based Language Teaching (TBLT) and ecolinguistic theory, this Classroom Action Research (CAR) was conducted in two cycles, involving 25 purposively selected students. The intervention centered around meaningful, environmentally-themed writing tasks that aimed to enhance students' writing abilities while fostering ecological awareness. Findings showed significant improvement across five key areas of writing: content relevance, vocabulary use, text organization, language accuracy, and mechanics. Quantitative data revealed an average increase of 20% in writing scores, with the greatest gains in vocabulary and organization. Qualitative data indicated increased learner motivation, autonomy, and use of ecological vocabulary. Thematic analysis also highlighted the development of critical thinking and environmental responsibility. The integration of ecolinguistic themes provided real-world relevance, making the writing process more engaging and meaningful. This study concludes that ETBAs are an effective and transformative strategy for enhancing both linguistic competence and ecological consciousness in EFL contexts.